Geno- and cytotoxicity of salinomycin in human nasal mucosa and peripheral blood lymphocytes. Issue 4 (June 2015) - Scherzad, Agmal; Hackenberg, Stephan; Schramm, Carolin; Froelich, Katrin; Ginzkey, Christian; Hagen, Rudolf; Kleinsasser, Norbert
Highlights Salinomycin induces cytotoxic effects in human non-malignant cells at 20 μM. Genotoxic potential was not found. The secretion of IL-8 was attenuated at sub-toxic concentrations. Toxicity occurs at concentrations relevant for cancer stem cell therapy.